Groundwater lowering for construction of the Kilsby Tunnel, UK – geological and geotechnical aspects. Issue 4 (1st December 2021) - Preene, Martin; Chrimes, Mike M
Abstract : The Kilsby Tunnel, constructed in the 1830s, faced severe problems when a section of the tunnel, almost 400 m long, encountered unstable 'quicksand' conditions. The engineer for the project, Robert Stephenson, developed an extensive groundwater lowering scheme, unique for the time, using steam engines pumping from multiple shafts, to overcome the quicksand. Modern geological information indicates most of the tunnel was in Middle Lias bedrock, but the 'quicksand' section passed through a buried channel of water-bearing sand of glacial origin. In the early nineteenth century, the impact of glacial processes on British geology was not widely accepted and, based on contemporary geological knowledge, Stephenson's problems appear to be genuine unforeseen ground conditions, not predicted by his experienced advisers. It seems just random chance that trial borings missed the buried channel of sand. The work at Kilsby was two decades before Darcy's law established the theoretical understanding for groundwater flow, and 90 years before Terzaghi's effective stress theory described how reducing pore water pressures changed 'quicksand' into a stable and workable material. Despite the lack of existing theories, Stephenson used careful observations and interpretation of groundwater flow in the 'quicksand' to navigate the tunnel project to a successful conclusion.